2004
DOI: 10.1007/s00425-004-1265-y
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of malate accumulation and the endogenous rhythms of gas exchange in the Crassulacean acid metabolism plant Kalancho� daigremontiana: testing the tonoplast-as-oscillator model

Abstract: In continuous light, leaves of the Crassulacean acid metabolism (CAM) plant Kalanchoë daigremontiana Hamet et Perrier exhibit a circadian rhythm of CO2 uptake, stomatal conductance and leaf-internal CO2 pressure. According to a current quantitative model of CAM, the pacemaking mechanism involves periodic turgor-related tension and relaxation of the tonoplast, which determines the direction of the net flux of malate between the vacuole and the cytoplasm. Cytoplasmic malate, in turn, through its inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
(54 reference statements)
2
22
0
Order By: Relevance
“…However, Wyka et al (2004) found that preventing nocturnal malate accumulation in Kalanchoë daigremontiana did not cause the predicted phase delays generated by the aforementioned computer model. The authors conclude that their results rule out vacuolar malic acid accumulation as the central pacemaking process in Kalanchoë (Wyka et al, 2004). The current paradigm is that the central circadian oscillator responsible for all rhythmic outputs consists of a discrete suite of genes, which form an autoregulatory negative feedback loop.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…However, Wyka et al (2004) found that preventing nocturnal malate accumulation in Kalanchoë daigremontiana did not cause the predicted phase delays generated by the aforementioned computer model. The authors conclude that their results rule out vacuolar malic acid accumulation as the central pacemaking process in Kalanchoë (Wyka et al, 2004). The current paradigm is that the central circadian oscillator responsible for all rhythmic outputs consists of a discrete suite of genes, which form an autoregulatory negative feedback loop.…”
mentioning
confidence: 87%
“…Computer modeling of this biophysical oscillator has demonstrated that it could sustain robust rhythmicity of CAM over a range of temperatures (Lü ttge, 2000). However, Wyka et al (2004) found that preventing nocturnal malate accumulation in Kalanchoë daigremontiana did not cause the predicted phase delays generated by the aforementioned computer model. The authors conclude that their results rule out vacuolar malic acid accumulation as the central pacemaking process in Kalanchoë (Wyka et al, 2004).…”
mentioning
confidence: 98%
“…Since the first discovery of PPCK activity and its circadian control in 1991 (Carter et al, 1991), through the subsequent cloning and characterization of the gene encoding this remarkable protein kinase in 1999 (Hartwell et al, 1999), there has been a long-held assumption that this circadian clock-controlled kinase is crucial for the temporal coordination and optimization of nocturnal atmospheric CO 2 fixation in CAM species, and the associated persistent circadian rhythm of CO 2 exchange observed under constant conditions in CAM species such as K. fedtschenkoi and K. daigremontiana (Wilkins, 1992;Nimmo, 2003;Wyka et al, 2004;Hartwell, 2006). However, it has not been possible previously to perturb genetically the level of PPCK activity and dark period PPC phosphorylation in a CAM species; thus, it has not been possible to test the validity of this long held assumption about the pivotal role of PPCK in the circadian control of CAM.…”
Section: Impact Of Silencing Kfppck1 On Circadian Rhythms Of Cam Co 2mentioning
confidence: 99%
“…CAM represents an noteworthy example of circadian clock specialisation and is one of the best-characterised physiological rhythms in plants (Wilkins 1992;Lüttge 2003;Wyka et al 2004). The presence of the CAM enzymatic machinery within a single cell requires strict temporal control of the competing carboxylation reactions by PEPC and RUBISCO.…”
Section: Circadian Clock Specialisation During Cam Evolutionmentioning
confidence: 99%